Adverse events of endoscopic ultrasound‐guided fine‐needle aspiration for histologic diagnosis in Japanese tertiary centers: Multicenter retrospective study. Issue 7 (15th January 2021) - Kanno, Atsushi; Yasuda, Ichiro; Irisawa, Atsushi; Hara, Kazuo; Ashida, Reiko; Iwashita, Takuji; Takenaka, Mamoru; Katanuma, Akio; Takikawa, Tetsuya; Kubota, Kensuke; Kato, Hironari; Nakai, Yousuke; et al.
Abstract : Background and Aims: Endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) is used for the histopathological diagnosis of any type of gastrointestinal disease. Few adverse events are experienced with this procedure; however, the actual rate of adverse events remains unclear. This study aimed to clarify the current status of cases that experienced adverse events related to the EUS‐FNA procedure used for histopathologic diagnoses. Methods: A retrospective analysis of cases with EUS‐FNA‐related adverse events in Japanese tertiary centers was conducted by assessing the following clinical data: basic case information, FNA technique, type of procedural adverse events, and prognosis. Results: Of the 13, 566 EUS‐FNA cases overall, the total number of cases in which adverse events related to EUS‐FNA occurred was 234. The incidence of EUS‐FNA‐related adverse events was 1.7%. Bleeding and pancreatitis cases accounted for 49.1% and 26.5% of all adverse events, respectively. Bleeding was the most common adverse event with only seven cases requiring blood transfusion. In cases with neuroendocrine tumors, pancreatitis was the most frequent adverse event. Needle tract seeding because of EUS‐FNA was observed during the follow‐up period in only 0.1% of cases with pancreatic cancer. There was no mortality because of adverse events caused by EUS‐FNA. Conclusions: This study revealed that the adverse events‐related EUS‐FNA for histopathologic diagnoses were not severe conditions, and had low incidence.